Influence of SDS on the Growth of Natural Gas Hydrates in a Sand Bed Depending on Saturation and Mineralization of Pore Moisture - Reshetnikov, Aleksey M. (Recent Innovations in Chemical Engineering, 2024)
Introduction: Evaluate the effect of SDS on induction time and conversion of water to hydrate in a porous medium model depending on the saturation and salinity of pore moisture. Methods: The work presents data on the formation of natural gas hydrates in sand bed fraction of 200-500 μm. The silica sand was saturated with water, solutions of SDS or NaCl, or a mixture of these. The saturation was 50% or 100%. The experiments were carried out under isochoric conditions at a temperature of 275 K and an initial pressure of 8 MPa. Results: It was shown that the main hydrate formation occurred in the first 60 minutes. The addition of SDS 0.05-0.2 wt.% in the sand bed does not exhibit a promoting effect, as was previously shown for pure water. The addition of NaCl 3 wt.% reduces the conversion of water to hydrate by 1.6 and 2 times for 50% and 100% saturation of the sand bed. Conclusion: The optimal concentration of the SDS additive to the salt solution has been found to reduce the inhibitory effect of the salt. The data obtained can be used to develop technologies for storing and transporting natural gas using sand and seawater.
Keywords: Gas hydrate